EFFECT OF FLUORIDE SOLUTION ON SALIVARY AMYLASE ACTIVITY - Enny Willianti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
Fluoride has the benefit on the tooth to inhibit caries. Fluoride is systemically incorporated into the crystal lattice of enamel by exchanging positions with the hydroxyl ion to result in formation of fluorapatite. Fluoride used locally may inhibit tooth demineralization, one of the mechanism is that fluoride is suspected to inhibit salivary amylase activity.